Protocol for tandem enrichment of ubiquitinated, phosphorylated, and glycosylated peptides with SCASP-PTM - Zhan-Peng Lin; Yu-Yang Wang; Chengwen Wen; Kaijie Zhang; Xiangyu Chen; Xu Liang; Wan-Yue Luo; Changchuan Xie; Chuan-Qi Zhong (STAR Protocols, 2025)
Summary: Here, we present a protocol for the tandem enrichment of ubiquitinated, phosphorylated, and glycosylated peptides from one sample using the SCASP-PTM (SDS-cyclodextrin-assisted sample preparation-post-translational modification) approach. We detail the steps for preparing samples for protein extraction and digestion, followed by the enrichment of ubiquitinated, phosphorylated, and glycosylated peptides in a serial manner without intermediate desalting. We then describe procedures for desalting prior to mass spectrometric analysis.For complete details on the use and execution of this protocol, please refer to Lin et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.